Participative Budgeting, Employee Motivation and Budgetary Slack in Private Sector in Indonesia - Carolina, Yenni (Universitas Pendidikan Indonesia, 2020)
This research was conducted to evaluate and analyze budgeting practices in the private sector, especially in the banking sector. This study analyzes the relationship between employee involvement in the budgeting process and budgetary slack practices through employee motivation. Participatory budgeting can make employees more motivated because employees will feel needed and their opinions are heard. As a result, employees reduce or eliminate dysfunctional behavior, namely budgetary slack. The data collection technique used was a questionnaire. The questionnaire was filled out by supervisors or managers at banks in Bandung. Questionnaires that can be processed are 33 questionnaires. The data analysis technique used is Structural Equation Modeling-PLS (SmartPLS 3.0). Hypothesis testing results indicated that the two research hypotheses can be accepted..